Financial literacy, access to digital finance and performance of SMEs: Evidence From Central region of Ghana - Stephanie Efua Frimpong; Gloria Kakrabah-Quarshie Agyapong; Daniel Agyapong (Cogent Economics & Finance, 2022)
This paper expands on financial literacy, access to digital finance, and SME performance in the Central Region of Ghana. First, the study analysed SMEs' digital platform knowledge and utilisation. It examined the relationship between financial literacy, access to digital finance, and SME performance. The paper discussed the mediating influence of access to digital finance on SMEs' financial literacy and performance. The study employed the quantitative research approach. Using the purposive sampling technique, a total of 400 responses were gathered from SMEs in Cape Coast, Mankessim, Assin Fosu, Agona Swedru, and Kasoa. The study used self-administered questionnaires to collect data. SPSS was employed to evaluate descriptive statistics. Results show that SMEs in the study areas use Mobile Money more than any other digital platform. PLS-SEM was used to investigate the relationship between financial literacy, digital finance, and SME performance. It was found that financial literacy positively affects access to digital finance. Also, access to digital finance improved performance. Access to digital finance mediates the relationship between financial literacy and SME performance. Access to digital finance is as crucial as financial literacy for increasing performance. Therefore, using digital platforms to trade would boost business performance. Digital trading platform providers should improve advertising and make their systems user-friendly.
Keywords: 330; Financial literacy; access to digital finance; performance of SMEs